Relationship Between Sleep Duration and Coronary Artery Disease in Older Adults - Pelin ÜNSAL; Mert EŞME; Cafer BALCI; Gözde ŞENGÜL AYÇİÇEK; Burcu BALAM YAVUZ; Meltem HALİL; Mustafa CANKURTARAN (Ahi Evran Medical Journal, 2023)
Purpose: Insomnia, a frequent geriatric syndrome, is thought to be linked with coronary artery disease and increased mortality. The aim of our study was to examine the relationship between sleep duration and coronary artery disease (CAD) and cardiovascular risk factors.